Pharyngolaryngeal amyloidosis – 4 cases report - Estêvão, Roberto (2012)
Amyloidosis is characterized by extracellular deposition of abnormal protein, with unknown etiology. This disease can affect any part of the body, but rarely appears in the upper aero-digestive tract. At this level it is more frequent in the larynx and extremely rare within the nasopharynx and oropharynx. It has a benign behavior when localized, but may have a poor prognosis in systemic cases. The authors present a case of primary amyloidosis at the nasopharynx and oropharynx, as well as a brief review of previous cases of localized amyloidosis documented in the Department of Otolaryngology at Senhora da Oliveira Hospital in Guimarães. The authors also intend to alert to the existence of this rare disease with variable clinical manifestations, and the importance of excluding systemic involvement. The current report describes a clinical case of nasooropharyngeal amyloidosis recently managed at the Institution. A description of three other patients with amyloidosis involving the ORL region and a review of the literature are also included.